The Existence Of The "Celah-Celah Langit" Community Through Theater Art As A Manifestation Of Civic Responsibility - Disya Dwi Nurhidayah; Kayla Putri Wilfi; Tria Mutiara R.S; Sapriya Sapriya; Syaifullah Syaifullah; Aang Supriatna (Jurnal Scientia, 2024)
This research aims to understand the role of cultural communities, especially the Celah-Celah Langit Community, in establishing social responsibility in society through the programs they promote. The method used in this research is a descriptive qualitative method, which will focus on processing data descriptively to provide an in-depth picture of the phenomenon being studied. The research techniques carried out included field studies through direct observation in the field and direct interviews with members of the Celah-Celah Langit Community. The research results show that the Celah-Celah Langit Community provides a space for expression for the surrounding community through their works of art. Many of these works are inspired by problems close to society, and not only from the themes, but also from the artistic aspects of the performances which are chosen to suit people's daily lives. In its creative process, this community involves the surrounding community, so that the community can be part of the works created and provide aspirations. Community participation in this community helps increase community awareness of current issues. This results in a sense of responsibility to play an active role in bringing about change in society. Thus, it can be concluded that cultural communities such as the Celah-Celah Langit Community play an important role in establishing social responsibility in society through the arts programs they promote.